2013
DOI: 10.5194/osd-10-1765-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Numerical modelling of physical processes governing larval transport in the Southern North Sea

Abstract: A three-dimensional hydrodynamic model (GETM) was coupled with a particle tracking routine (GITM) to study the inter-annual variability in transport paths of particles in the North Sea and English Channel. For validation, a comparison with observed drifter trajectories was made. The aim was to investigate to what extent variability in the hydrodynamic conditions alone (reflecting passive particle transport) contributed to inter-annual variability in transport of eggs and larvae. In this idealized study, no a-p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Comparing modelled drift routes with observations is generally more difficult than comparing the OCM derived fluxes or temperatures as specific field measurement are lacking against which results can be compared. Sub surface Argo floats mainly represent the combined effect of wind and surface currents and also show high variability in observed trajectories (Hill et al, 2008;Tiessen et al, 2014). In model drift studies generally A C C E P T E D M A N U S C R I P T 5 several thousand particles are released while in reality experiments are restricted to much smaller numbers, although the observed diversity of routes taken by the buoys indicates that many more floats would be needed for a representative analysis.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing modelled drift routes with observations is generally more difficult than comparing the OCM derived fluxes or temperatures as specific field measurement are lacking against which results can be compared. Sub surface Argo floats mainly represent the combined effect of wind and surface currents and also show high variability in observed trajectories (Hill et al, 2008;Tiessen et al, 2014). In model drift studies generally A C C E P T E D M A N U S C R I P T 5 several thousand particles are released while in reality experiments are restricted to much smaller numbers, although the observed diversity of routes taken by the buoys indicates that many more floats would be needed for a representative analysis.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…year-to-year variability (Lacroix et al, 2016), modelled and observed distribution of plaice larvae (Hufnagl et al, 2013) or drift of buoys (Tiessen et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the impact of pelagic dispersal on connectivity has been studied using particle tracking approaches that model both hydrodynamics and larval behaviour. These models have been used to assess recruitment of commercial fish species 15 20 and jellyfish 21 . Corridors between structures such as pipelines provide a mechanism for colonisation of reef species that do not have pelagic dispersal 6 .…”
Section: Introductionmentioning
confidence: 99%
“…This paper focusses on connectivity through planktonic life stages of several different sedentary species commonly found in association with man-made structures using an existing particle tracking model 20 , 21 . The General Individuals Transport Model (GITM) includes physical particle advection based on current fields from hydrodynamic models, diffusion, biological development, and behaviour 18 , 21 .…”
Section: Introductionmentioning
confidence: 99%